Effects of transcutaneous electrical acupoint stimulation on early postoperative pain and recovery: a comprehensive systematic review and meta-analysis of randomized controlled trials - Tan, Shi-Yan; Jiang, Hua; Ma, Qiong; Ye, Xin; Fu, Xi; Ren, Yi-Feng; You, Feng-Ming (Frontiers in Medicine, 2024)
Background Previous studies have indicated beneficial outcomes of transcutaneous electrical acupoint stimulation (TEAS), but high-quality and comprehensive meta-analyses are lacking. The aim was to quantitatively analyze the efficacy and safety of perioperative TEAS on postoperative pain and recovery. Methods PubMed, Web of Science, EMBASE, and the Cochrane Library were searched through July 2022. Randomized controlled trials (RCTs) that examined the perioperative application of TEAS in adults compared with sham-TEAS and/or non-TEAS were eligible. Cumulative analgesic consumption within 24 h and rest pain scores at 2, 6, 12, and 24 h postoperatively were the two co-primary outcomes. Results Seventy-six RCTs (n = 9,665 patients) were included. Patients treated with TEAS experienced a reduction in clinical importance in cumulative analgesic (morphine equivalent) consumption (WMD: −14.60 mg, 97.5% CI: −23.60 to −5.60; p < 0.001) and a reduction in statistical importance in rest pain scores at multiple time points within the first 24 postoperative hours. The secondary outcome analysis also identified clinically significant recovery benefits to TEAS during the first 24 h after surgery. Furthermore, TEAS could effectively reduce opioid-related side effects and did not increase serious side effects. Conclusion This article describes current evidence about TEAS intervention on early postoperative pain and recovery. The results support the effectiveness of TEAS, but more high-quality evidence of clinical applicability is also needed. Systematic review registration PROSPERO (CRD42021249814).